Is it possible to modulate fasciculation potential firing in ALS?. Issue 3 (March 2016) - de Carvalho, M.; Turkman, A.; Pinto, S.; Swash, M.
Abstract : Fasciculation is an important clinical feature in ALS. In spite of large numbers of papers regarding their origin, morphology and stability, their modulation by external interventions has not been studied. We aimed to approach this issue. We studied the first dorsal interosseus muscle (FDI) of 31 ALS patients in whom this muscle had normal strength, 23 ALS patients with slightly weak FDI (ALS4), 10 patients with benign fasciculation syndrome (BFS) and 6 patients with spinal muscle atrophy (SMA). FP frequency was recorded thorough surface electrodes in 2 min recordings. Following a baseline recording, FP frequency was evaluated in the subsequent randomized conditions: baseline; immediately after a 1 min maximal isometric contraction; immediately after application of a 1 Hz train of 50 supramaximal stimuli to the distal ulnar nerve; immediately after stimulation of the sensory branch of the radial nerve (at 2.5 cutaneous threshold, 20 Hz, 600 stimuli). Baseline recording was reliable. There was a significant increase in FP frequency after sensory stimulation in ALS4 ( p  = 0.01), but other modulatory interventions had no effect. In SMA an increase in FP frequency was observed following sensory stimulation. In BFS, FPs frequency was not changed. Activation of sensory afferent fibers increases the excitability of affected lower motor neurons